Рец. на кн.: Антропология культуры: Вып. 5. К 85-летию академика РАН Вячеслава Всеволодовича Иванова [Antropologiia kul’tury. Vyp. 5: K 85-letiiu akademika RAN Viach. Vs. Ivanova. A review article.] - Daria Dorving; Yelena Zemskova; Maria Posledova; Anna Rubtsova (Slavica Revalensia)
This review summarizes 18 articles published on the occasion of Vyacheslav Vsevolodovich Ivanov’s 85th birthday. The articles’ scope varies from cultural anthropology to structuralist poetics, and the legacy of the Russian literary and scholarly avant-garde.